Is the systematic use of mapping systems during His Bundle catheter ablation cost‐effective? A single‐center experience. Issue 4 (30th June 2020) - Marini, Massimiliano; Ravanelli, Daniele; Martin, Marta; Battisti, Valentina; Quintarelli, Silvia; Guarracini, Fabrizio; Coser, Alessio; Menegotti, Loris; Bonmassari, Roberto
Abstract: Aim: Three‐dimensional (3D) nonfluoroscopic mapping systems (NMSs) are generally used during the catheter ablation (CA) of complex arrhythmias. We evaluated the efficacy, safety, and economic advantages of using NMSs during His‐Bundle CA (HB‐CA). Methods: A total of 124 consecutive patients underwent HB‐CA between 2012 and 2019 in our EP Laboratory. We compared two groups: 63 patients who underwent HB‐CA with fluoroscopy alone from 2012 to 2015 (Group I) and 61 patients who underwent HB‐CA with the aid of NMSs from 2016 to 2019 (Group II). Two cost‐effectiveness analyses were carried out: the alpha value (AV) (ie, a monetary reference value of the units of exposure avoided, expressed as /man Sievert) and the value of a statistical life (VSL) (ie, the amount of money that a community would be willing to pay to reduce the risk of a person's death owing to exposure to radiation, it is not the cost value of a person's life). The cost reduction estimated by means of both these methods was compared with the real additional cost of using NMSs. Results: The use of NMS resulted in reduced fluoroscopy time in Group II median 1.35 min in comparison with Group I median 4.8 min ( P < .05). The effective dose reduction (ΔE) was 1.16 milli‐Sievert. Conclusion: The use of NMS significantly reduces fluoroscopy time. However, the actual reduction is modest and in our EP Laboratory this reduction is not cost‐effective. Indeed, when the ΔE is referred to country and agency tables for absolute values of AV or VLS, it is not economically advantageous in almost all cases. Abstract : We evaluated the efficacy, safety and economic advantages of using 3D non‐fluoroscopic mapping systems during His‐Bundle CA.The use of mapping systems significantly reduces fluoroscopy time. However, the actual reduction is modest and it is not cost‐effective.